Faunistic analysis of the species of anastrepha schiner (diptera: Tephritidae) in three municipalities of the state of roraima, Brazil - Marsaro, Alberto Luiz; Nascimento, Danilo Baia do; Ronchi-Teles, Beatriz; Adaime, Ricardo (Revista Brasileira de Biologia, 2012)
The purpose of this work was to describe the population patterns of Anastrepha in three municipalities of the state of Roraima, Brazil, via faunistic analysis. Weekly collections were performed from January through December 2008, using McPhail traps containing 5% hydrolysed protein, in domestic orchards in the municipalities of Boa Vista, Bonfim and Pacaraima. We captured 301 females of Anastrepha in Boa Vista, 212 in Bonfim, and 167 in Pacaraima. Boa Vista presented the highest species richness (S = 10) and Pacaraima the lowest (S = 4). Anastrepha striata was the predominant species in Boa Vista (47.18%) and Pacaraima (65.87%), whereas A. obliqua predominated in Bonfim (46.23%). Boa Vista presented the highest Shannon-Wiener diversity index (H' = 1.19) and Margalef index (α = 1.58), and Bonfim presented the highest Pielou's evenness index (J' = 0.69). In Pacaraima the cumulative curves reached stability, confirming that the observed and expected species richness were the same. In the other two municipalities, the curves showed a moderate growth, suggesting that the sampling effort was not sufficient to produce an accurate depiction of species richness. In this study, Anastrepha zernyi is reported for the first time in Roraima.
Análise faunística das espécies de anastrepha schiner (diptera: Tephritidae) em três municípios do estado de roraima, Brasil
Keywords: Animals; Biodiversity; Classification; Female; Population Density; Tephritidae; Animal; Biodiversity; Female; Population Density; Tephritidae; Anastrepha; Anastrepha Obliqua; Anastrepha Striata; Diptera; Tephritidae